Comparisons between Caucasian-validated and Chinese-validated photo-numeric scales for assessing facial wrinkles - Ng, Jun Yan; Zhou, Hongyu; Li, Tianqi; Chew, Fook Tim (Scientific reports, 2024)
Skin ageing results in wrinkling. In this study, we discuss four types of facial wrinkles: Crow’s Feet wrinkles, forehead wrinkles, glabellar frown wrinkles, and nasolabial folds. These four phenotypes can be assessed either with a photo-numeric scale developed and validated on Caucasian skin (i.e., Caucasian scale) or with a photo-numeric scale developed and validated on Chinese skin (i.e., Chinese scale). As Caucasian and Chinese skin have inherent differences, the main objective of this study is to determine whether these inherent differences affect the suitability of evaluating facial wrinkles on ethnic Chinese skin with a Caucasian scale. Three trained assessors studied four types of wrinkles on the faces of 1,081 ethnic Chinese young adults from the Singapore/Malaysia Cross-sectional Genetics Epidemiology Study (SMCGES). We found that Caucasian scales and Chinese scales are concordant (Spearman’s Rank Correlation (ρ) values: 0.53–0.80) and the level of agreement between the Caucasian scales and Chinese scales is moderately high (Cohen’s Kappa (κ) values: 0.40–0.49). When tested on ethnic Chinese skin, both the Caucasian scale and the Chinese scale are largely consistent in showing presence or absence of a given facial wrinkle (Area under curve (AUC) values: 0.79–0.90). All assessors are highly internally consistent (Weighted Kappa (κ w ) values: 0.686–0.992). Our results build confidence that four types of facial wrinkles on ethnic Chinese faces can be assessed with Caucasian scales. To the best of our knowledge, Chinese scales for facial wrinkles beyond the four types discussed here have yet to be developed. Caucasian scales for these other facial wrinkles will also need to be tested for their suitability to be used on ethnic Chinese skin as and when more Chinese scales are developed.